THE EFFECTIVENESS OF NEURODYNAMIC TECHNIQUE (TENSIONING AND SLIDING) AND ULTRASOUND THERAPY TO REDUCE SYMPTOMS ON CARPAL TUNNEL SYNDROME PATIENTS: A CASE REPORT - Khotimah, Ulfah Khusnul; Pristianto, Arif; Rochmaningtyas, Putri (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Carpal Tunnel Syndrome (CTS) is a peripheral neuropathy caused by entrapment on the median nerve in the carpal tunnel resulting in limited nerve mobility. The aim of this study is to find out the effectiveness of the neurodynamic technique (tensioning and sliding) and ultrasound therapy to reduce symptoms in CTS patients. Case Presentation: The patient was a 47 years old woman with sensory impairment and decreased functional ability. Sensory impairment includes pain, paresthesias, and numbness in the palm and thumb to the ring finger. Management and Outcome: Treatment given was a conservative treatment by physiotherapy in the form of neurodynamic technique (tensioning and sliding) and ultrasound therapy. The instruments used were the Numeric Pain Rating Scale to measure the pain and Boston Carpal Tunnel Questionnaire to measure the severity of symptoms and functional ability. Discussion: The results obtained were the decrease of tenderness T1: 3 to T4: 2, motion pain T1: 3 to T4: 2, and increased functional ability of the patient. Conclusion: The addition of hand splinting use during working with giving neurodynamic technique (tensioning and sliding) and ultrasound therapy can effectively reduce pain and increase functional ability.